Multi-omics analysis of the biological mechanism of the pathogenesis of non-alcoholic fatty liver disease - Lin, Jie; Zhang, Ruyi; Liu, Huaie; Zhu, Yunzhen; Dong, Ningling; Qu, Qiu; Bi, Hongyan; Zhang, Lihua; Luo, Ou; Sun, Lei; Ma, Mengjuan; You, Jing (Frontiers in Microbiology, 2024)
Background Non-alcoholic fatty liver disease (NAFLD) is a type of liver metabolic syndrome. Employing multi-omics analyses encompassing the microbiome, metabolome and transcriptome is crucial for comprehensively elucidating the biological processes underlying NAFLD. Methods Hepatic tissue, blood and fecal samples were obtained from 9 NAFLD model mice and 8 normal control mice. Total fecal microbiota DNA was extracted, and 16S rRNA was amplified, to analyze alterations in the gut microbiota (GM) induced by NAFLD. Subsequently, diagnostic strains for NAFLD were screened, and their functional aspects were examined. Differential metabolites and differentially expressed genes were also screened, followed by enrichment analysis. Correlations between the differential microbiota and metabolites, as well as between the DEGs and differential metabolites were studied. A collinear network involving key genes-, microbiota-and metabolites was constructed. Results Ileibacterium and Ruminococcaceae, both belonging to Firmicutes; Olsenella, Duncaniella and Paramuribaculum from Bacteroidota; and Bifidobacterium, Coriobacteriaceae_UCG_002 and Olsenella from Actinobacteriota were identified as characteristic strains associated with NAFLD. Additionally, differentially expressed metabolites were predominantly enriched in tryptophan, linoleic acid and methylhistidine metabolism pathways. The functions of 2,510 differentially expressed genes were found to be associated with disease occurrence. Furthermore, a network comprising 8 key strains, 14 key genes and 83 key metabolites was constructed. Conclusion Through this study, we conducted a comprehensive analysis of NAFLD alterations, exploring the gut microbiota, genes and metabolites of the results offer insights into the speculated biological mechanisms underlying NAFLD.